Prevalence of Chagas Disease Among Blood Donors in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto Nigeria - Onuigwe, Festus Uchechukwu *, Udomah, F.P., Yakubu, Abdulrahaman, Isaac, Zama, Adias, Teddy Charles, Ibrahim, Kwaifa, Buhari, Hauwa, Okwesili, Augustine, Ahmed, Marafa , Imoru, Momodu, Erhabor, Osaro, Bagudo, Aliyu, Okorie, Hope (Sokoto Journal of Medical Laboratory Science)
Transfusion-transmissible infections (TTIs) are the greatest threats to blood transfusion safety and pose a serious public health problem in Nigeria. Chagas disease caused by Trypanosome cruzi is one of the TTIs and can be transmitted through blood transfusion. In this study, we investigated the prevalence of Chagas disease among 239 consecutively recruited blood donors aged 18 to 65 years and mean age 28.8± 4.4 years using rapid diagnostic kits from CTK Biotech Inc. USA. From this study, we observed a prevalence of 19.7% for Chagas disease among blood donors in UDUTH Sokoto. The prevalence of Chagas based on the type of blood donors was not statistically significant (p>0.05). The prevalence of Chagas was significantly higher among the single subjects (p<0.05). There was a statistically significant association between age and the prevalence of Chagas disease among blood donors (p=0.05). This study demonstrates a substantial risk of Chagas disease as one of the transfusion-transmissible infections in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto North-Western, Nigeria. We recommend that effort be made to recruit and retain low risk voluntary non-remunerated donors and the need to routinely screen blood donors for Chagas disease. There is the need for a larger study to determine the prevalence of Chagas disease among blood donors in Nigeria using both Rapid kit and ELISA. Non- endemic countries receiving immigrants from the endemic ones should develop policies to protect organ recipients in particular and transfusion recipients in general from T. cruzi infection.